Keamanan Manusia Berbasis Ketahanan: Studi tentang Anak-Anak Migran Indonesia dan Muhammadiyah di Malaysia - Muhammad Fajhriyadi Hastira; Ali Maksum (LPPM Universitas Negeri Surabaya, 2025)
This study aims to analyze the human security threats experienced by Indonesian migrant children in Malaysia, as well as to examine how Muhammadiyah plays a role in building their resilience through community education. The limited access of migrant children to formal education, health services, and legal protection is a significant issue being studied. Using a qualitative approach with a case study design, this research relies on literature studies and document analysis from international agency reports, Indonesia-Malaysia bilateral policies, and documentation of Muhammadiyah's education programs in Sabah and Sarawak. Data analysis was conducted using thematic techniques to identify vulnerability and adaptive capacity patterns at three levels: individual, community, and institutional. The results show that despite facing structural vulnerability due to their undocumented status, migrant children can develop adaptive strategies through social networks, community solidarity, and alternative schools. Muhammadiyah plays a significant role in providing community-based education that not only builds academic capacity but also strengthens the social and spiritual identity of migrant children. These findings contribute to developing the concept of resilience-based human security, broadening theoretical understanding while offering a practical model for protecting migrant children. The study recommends the need for multi-stakeholder collaboration and the strengthening of ASEAN regional policies to make the protection of migrant children more inclusive and sustainable. Keywords: Barbie Film, Feminism, Resistance, South Korea.